Identifikasi Karakter Sosial Pada Wirausaha Sosial (Studi Kasus: CV. Energi Persada, PT. Greeneration Indonesia, Amygdala Bamboo Dan CV. Wahana Putra Ideas Tahun 2017) - Riyan Rahmat Yanuar; Grisna Anggadwita (Lembaga Penelitian Universitas Langlangbuana, 2019)
Unemployment and Poverty are the main issues in most countries, including Indonesia. It is a general problem, considering the high unemployment level is the main problem in every developing country. Therefore, social entrepreneurs becomes necessary. Indonesia needs figures that can help the government by not only helping the society but also by directing them to achieve a better economy and social life individually. Social entrepreneur is supposed to be a solution to accelerate the decrease of unemployment and poverty rate. That’s because social entrepreneurs offer advantageous benefits from only providing job vacancy. Entrepreneurship gives vast benefits because it doesn’t only deal with the employees, from work partners, but also the whole society. Thus, a research about social characters in order to find out an individual characters that distinguish scoial entrepreneurs from the mediocre ones. This research aims to find out the idea of social entrepreneurship and to identify the social characters within social entrepreneurs in Bandung City i.e., CV. Energi Persada, PT. Greeneration Indonesia, Amygdala Bamboo, dan CV. Wahana Putra Ideas, with variables of Social Value, Civil Society, Innovation, Economy Activity, dan Social Outcome. The method in this research is qualitative method. Twelve people; Three people from each company, consisted of two internal members of the company and one external member of the company which is a citizen involved with the company, are interviewed for the research. Data for the research are collected from interview and report with the involved ones. Data are analyzed by the researchers, referring to the theory. Based on the result of the data processing from the four entrepreneurs, All social entrepreneurship i.e. CV. Energi Persada, PT. Greeneration Indonesia, Amygdala Bamboo, dan CV. Wahana Putra Ideas, have done their business based on the five variables of social characters i.e., Social Value, Civil Society, Innovation, Economy Activity, dan Social Outcome. Based on result of the the research, becoming a social entrepreneur requires social characters, such as Social Value, Civil Society, Innovation, Economy Activity, dan Social Outcome. Social entrepreneurs can be a partner for the government to develop the country, as social entrepreneurs are proven capable decreasing the poverty and unemploment level.